To show the distribution of \(5\) to the expression \((x - 1)\), you'll multiply each term within the parentheses by \(5\). Here's how the equation breaks down step by step:
-
Distribute the \(5\) to both \(x\) and \(-1\): \[ 5(x - 1) = 5 \cdot x - 5 \cdot 1 \] This simplifies to: \[ 5x - 5 \]
-
Now, you can rewrite the original equation: \[ 5(x - 1) = 5x - 3 \] becomes: \[ 5x - 5 = 5x - 3 \]
-
Next, let's isolate the variable \(x\). Subtract \(5x\) from both sides: \[ 5x - 5 - 5x = 5x - 3 - 5x \] This simplifies to: \[ -5 = -3 \]
-
The equation \(-5 = -3\) is a contradiction; it is false and indicates that there are no solutions to the original equation.
In conclusion, the equation \(5(x - 1) = 5x - 3\) has no solutions.